A Cadaveric Study of Length of Trachea in Nepalese Population of Various Age Groups - Sharma, Nitasha; Khan, Gulam Anwar; Pandit, Ruku (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION :The trachea is centrally located membranocartilaginous unpaired hollow organ extending downwards as a continuation of the larynx. The study of the semorphometric variations is of profound clinical importance as it may help the clinicians to understand the etiology of several pulmonary diseases and the surgeons to deal with resection and reconstruction of the tracheobronchial tree. This knowledge is also helpful for smooth conduction of some maneuvers like endotracheal intubation and bronchoscopic procedures. MATERIALS & METHODS: A study of length of human trachea was undertaken in the Department of Anatomy, College of Medical Science Teaching Hospital, Bharatpur, Nepal from april 2012 to December 2013. Twenty nine specimens were collected out of which, sixteen were male and thirteen were female. The specimens were grouped into five age groups for both sexes. The length of trachea, was measured and, standard error (SE), standard deviation(SD) and test of significance were calculated using independent sample 't' test and multiple comparison test. RESULTS:The length of trachea, there was a rapid increase in length from 0-15 years group to 16-25 years group in both the sexes. Thereafter it exhibited very insignificant variations from 26-40 and 41-55 years group in both sexes. From 41-55 years age group to >55 years age group there was a slight increase in tracheal length in both sexes. CONCLUSION: The length of trachea varies with age and the results observed are comparatively less than written in standard books from foreign authors ,hence racial difference plays a key role in the length of trachea. Furthermore, we suggest more research is required in this field from our regional area. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15 17, page: 17-21